PENGEMBANGAN MEDIA PAPAN MAGNETIK MATERI ORGAN PERNAPASAN MANUSIA DAN FUNGSINYA UNTUK SISWA KELAS V DI SDN MANGGIS 2 PUNCU - Sakiya Salma Hamida; Dwi Nur Wenda, Dhian; Sri Mujiwati, Endang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
There is a goal of the research carried out to create magnetic board media as a learning medium with the sub-discussion of human respiratory organs and their functions for class V science lessons. In the research carried out the method applied is the research and development method and the research model used is the ADDIE type model. The levels of the ADDIE type model are analysis, design, development, implementation, evaluation. Data collection in the research carried out included validity data, practicality data and effectiveness data. The effectiveness test was carried out by class V students at SDN Manggis 2 Puncu and the research subjects were 23 students. The results of research on the development of magnetic board media are (1) magnetic board media received media validation results of 88%, material validation received a score percentage of 85%, learning tools received a score percentage of 88%, and questions received a score percentage of 88.57%, as well as the results the average percentage between the media validation score and the material validation score is 87.59% (2) magnetic board media obtained teacher response results of 94% and student response results of 91.30% which were included in the very practical category (3) in In the effectiveness test, there were 21 students who completed it while 2 students did not complete it. Apart from that, the average percentage score is 87.26% and the percentage of classical learning completion scores is 91.30%. Thus, magnetic board media can be stated as a valid, practical and effective medium.